2014
DOI: 10.1111/ejh.12286
|View full text |Cite
|
Sign up to set email alerts
|

CD20‐positive plasmablastic lymphoma with excellent response to bortezomib combined with rituximab

Abstract: As a distinct type of aggressive mature large B-cell lymphoma, plasmablastic lymphoma (PBL) poses diagnostic and treatment challenges. PBL is distinguished from other B-cell lymphomas by the presence of plasmacytic differentiation markers such as CD38, CD138, and MUM1. Clinically, PBLs from oral and extra-oral sites are rapidly progressive tumors with frequent relapse after treatment with standard diffuse large B-cell lymphoma regimens. Here, we report a near-complete response of one patient with relapsed PBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…55 Bortezomib alone and in combination with chemotherapy has been used with limited efficacy in HIV-positive and HIV-negative patients with relapsed PBL. [56][57][58][59][60][61][62] More recently, a case series of 3 previously untreated patients with PBL, 2 of them HIV-positive, has shown efficacy with the combination of bortezomib and dose-adjusted EPOCH. 63 The immunomodulator lenalidomide induced a temporary response in a patient with relapsed PBL.…”
Section: Current Treatment Options and Emerging Therapiesmentioning
confidence: 99%
“…55 Bortezomib alone and in combination with chemotherapy has been used with limited efficacy in HIV-positive and HIV-negative patients with relapsed PBL. [56][57][58][59][60][61][62] More recently, a case series of 3 previously untreated patients with PBL, 2 of them HIV-positive, has shown efficacy with the combination of bortezomib and dose-adjusted EPOCH. 63 The immunomodulator lenalidomide induced a temporary response in a patient with relapsed PBL.…”
Section: Current Treatment Options and Emerging Therapiesmentioning
confidence: 99%
“…Instead, more intensive regimens such as hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with methotrexate and cytarabine are typically used. In the very rare case that PBL expresses CD20, rituximab has been added to the chemotherapy regimen with an excellent response (10). Several groups have shown that patients with EBVpositive DLBCL have a worse prognosis when compared with patients with EBV-negative DLBCL, making EBV per se an independent adverse prognostic indicator (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented activity of the proteasome inhibitor bortezomib in PBL [12,13,14,15,16,17]. The anti-CD30 antibody brentuximab vedotin has also been shown to have activity in 1 report [18].…”
Section: Discussionmentioning
confidence: 99%